Development of a high-throughput UHPLC–MS/MS (SRM) method for the quantitation of endogenous glucagon from human plasma. (December 2014) - Howard, James W; Kay, Richard G; Tan, Tricia; Minnion, James; Ghatei, Mohammad; Bloom, Steve; Creaser, Colin S
Background: Published LC–MS/MS methods are not sensitive enough to quantify endogenous levels of glucagon.Results: An ultra high performance liquid chromatography-MS/MS (SRM) method for the quantitation of endogenous levels glucagon was successfully developed and qualified. A novel 2D extraction procedure was used to reduce matrix suppression, background noise and interferences. Glucagon levels in samples from healthy volunteers were found to agree with radioimmunoassay (RIA) derived literature values. Bland–Altman analysis showed a concentration-dependent positive bias of the LC/MS–MS assay versus an RIA. Both assays produced similar pharmacokinetic profiles, both of which were feasible considering the nature of the study.Conclusion: Our method is the first peer reviewed LC–MS/MS method for the quantitation of endogenous levels of glucagon, and offers a viable alternative to RIA-based approaches.